2020
DOI: 10.1002/jor.24824
|View full text |Cite
|
Sign up to set email alerts
|

Effects of human articular cartilage constituents on simultaneous diffusion of cationic and nonionic contrast agents

Abstract: Contrast-enhanced computed tomography is an emerging diagnostic technique for osteoarthritis. However, the effects of increased water content, as well as decreased collagen and proteoglycan concentrations due to cartilage degeneration, on the diffusion of cationic and nonionic agents, are not fully understood. We hypothesize that for a cationic agent, these variations increase the diffusion rate while decreasing partition, whereas, for a nonionic agent, these changes increase both the rate of diffusion and par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 47 publications
2
10
0
Order By: Relevance
“…Neither of these treatments replicates the type or pattern of degeneration associated with early-stage OA, and studies on human tissues will be required to determine how well this approach translates to the detection of clinically realistic degradation patterns. A recent study [53] found an inverse correlation between maximum concentration of gadoteridol, another non-ionic CA and collagen content in human articular cartilage at equilibrium, suggesting that patterns in human tissue may be similar to the ones presented here.…”
Section: Discussionsupporting
confidence: 84%
“…Neither of these treatments replicates the type or pattern of degeneration associated with early-stage OA, and studies on human tissues will be required to determine how well this approach translates to the detection of clinically realistic degradation patterns. A recent study [53] found an inverse correlation between maximum concentration of gadoteridol, another non-ionic CA and collagen content in human articular cartilage at equilibrium, suggesting that patterns in human tissue may be similar to the ones presented here.…”
Section: Discussionsupporting
confidence: 84%
“…39,40 Moreover, the diagnostic sensitivity of the cationic agent can be further enhanced with a non-ionic compound, nullifying the variation in the diffusion caused by changes in tissue water content and permeability. 41,42 Our results form a good basis to proceed on this path, as these show clear differences in ioxaglate partition values between lesions and healthy tissue, even though cationic agent have exhibited stronger correlation with PGs (R 2 = 0.83) than negatively charged agents (R 2 = 0.20). 19 In conclusion, in the current study the dual-contrast method was, for the first time, applied to evaluate the cartilage condition…”
Section: Discussionmentioning
confidence: 62%
“…One proposed alternative is to substitute ioxaglate with a cationic agent that diffuses into cartilage proportionally to the PG content 39,40 . Moreover, the diagnostic sensitivity of the cationic agent can be further enhanced with a non‐ionic compound, nullifying the variation in the diffusion caused by changes in tissue water content and permeability 41,42 . Our results form a good basis to proceed on this path, as these show clear differences in ioxaglate partition values between lesions and healthy tissue, even though cationic agent have exhibited stronger correlation with PGs ( R 2 = 0.83) than negatively charged agents ( R 2 = 0.20) 19 …”
Section: Discussionmentioning
confidence: 70%
“…The sample preparation for the present work did not include the use of any agent preventing cartilage degradation (i.e., antimycotic, antibiotic, protease inhibitors), unlike previous studies [ 17 , 18 , 20 , 21 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 33 , 35 , 36 ]. Though deterioration processes are expected to affect cartilage following the harvesting of samples, the use of preserving agents could alter cartilage pristine properties, including the interaction with CA4+.…”
Section: Discussionmentioning
confidence: 99%
“…A novel cationic iodinated contrast agent, CA4+, was specifically designed to electrostatically interact with glycosaminoglycans (GAGs) bound in proteoglycans [ 16 ]. In particular, the Coulomb attraction between negative fixed charges of GAGs and positively-charged CA4+ molecules showed superior contrast enhancement compared to commercially available contrast agents, (even at lower concentrations [ 17 , 18 , 19 ]), in animal [ 20 , 21 , 22 , 23 ] and human [ 24 , 25 , 26 , 27 , 28 , 29 ] samples, on several types of tissue containing GAGs [ 13 , 30 , 31 ] and cartilage tissue-engineered constructs [ 32 ]. The use of CA4+ was investigated in combination with synchrotron radiation as well, exploiting the high brilliance and monochromaticity of X-ray beam [ 33 , 34 , 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%